2022
DOI: 10.1021/acsaem.2c00623
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Photoinitiator Concentration on the Electro-optical Properties of Thiol–Acrylate-Based PDLC Smart Windows

Abstract: Polymer-dispersed liquid crystals (PDLCs), an indispensable class of electrically switchable materials, where nano- or microsized liquid crystal (LC) droplets are phase-separated from the polymer matrix, have been widely used in the fabrication of highly efficient and systematic smart windows. In this paper, we explored the effect of the photoinitiator concentration on the morphology and electro-optical properties of PDLC films based on thiol and acrylates. We prepared PDLC films using various concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Figure S4 showed that with the introduction of polymer walls, the t on decreased and the t off increased because the size of LC droplets increased (consistent with Figure S3). ,, …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure S4 showed that with the introduction of polymer walls, the t on decreased and the t off increased because the size of LC droplets increased (consistent with Figure S3). ,, …”
Section: Resultsmentioning
confidence: 99%
“…Figure S4 showed that with the introduction of polymer walls, the t on decreased and the t off increased because the size of LC droplets increased (consistent with Figure S3). 17,35,36 Figure 3 illustrated that the polymer walls could significantly improve the stability of reverse-mode PSLC films. The sparse and fine polymer networks were more easily destroyed after multiple cycles for the films without polymer walls.…”
Section: Effect Of the Introduction Of Polymer Walls On Electro-optic...mentioning
confidence: 99%
See 2 more Smart Citations
“…Polymer/liquid crystal (LC) composites have attained significant attention in the recent past because of the burgeoning interest in their potential photoelectrical applications, such as switchable windows, microlenses, reflective displays, multicolor displays, light shutters, and sensors. These composites are structurally divided into two types depending on the LC concentration: polymer-dispersed LC (PDLC) and polymer-stabilized LC (PSLC). , The former contains up to 80% LC content in the form of randomly oriented droplets dispersed in a phase-separated polymer framework. The latter, however, contains 90% or more LC content, and LC molecules are stabilized in the polymer network.…”
Section: Introductionmentioning
confidence: 99%